Association between ten-eleven methylcytosine dioxygenase 2 genetic variation and viral load in people with HIV. (1st March 2023) - Murray, Daniel D.; Grund, Birgit; MacPherson, Cameron R.; Ekenberg, Christina; Zucco, Adrian G.; Reekie, Joanne; Dominguez-Dominguez, Lourdes; Leung, Preston; Fusco, Dahlene; Gras, Julien; Gerstoft, Jan; Helleberg, Marie; et al.
Abstract : Introduction: Identifying genetic factors that influence HIV-pathogenesis is critical for understanding disease pathways. Previous studies have suggested a role for the human gene ten-eleven methylcytosine dioxygenase 2 (TET2) in modulating HIV-pathogenesis. Methods: We assessed whether genetic variation in TET2 was associated with markers of HIV-pathogenesis using both gene level and single nucleotide polymorphism (SNP) level association in 8512 HIV-positive persons across five clinical trial cohorts. Results: Variation at both the gene and SNP-level of TET2 was found to be associated with levels of HIV viral load (HIV-VL) consistently in the two cohorts that recruited antiretroviral-naïve participants. The SNPs occurred in two clusters of high linkage disequilibrium (LD), one associated with high HIV-VL and the other low HIV-VL, and were predominantly found in Black participants. Conclusion: Genetic variation in TET2 was associated with HIV-VL in two large antiretroviral therapy (ART)-naive clinical trial cohorts. The role of TET2 in HIV-pathogenesis warrants further investigation.